Direct evidence of CO2 softening effects on coal using nanoindentation. (1st September 2022) - Zhang, Guanglei; Ranjith, P.G.; Lyu, Qiao
Abstract: Sequestration of carbon dioxide (CO2 ) in deep coal seams has been identified as a promising technique to mitigate global warming with added benefit of enhancing coalbed methane recovery. Understanding coal structure and its reactivity with injected CO2 is important for CO2 sequestration in coal. Despite the long-standing hypothesis, there is no direct evidence of softening effects of CO2 on coal due to CO2 -coal interactions. Here, we used optical microscopy and nanoindentation to study changes in microstructures and nanoscale mechanical properties of untreated and CO2 -treated anthracite coal. Microscopic images indicated coal surface cracked after short-term treatment and then became highly wrinkled and distorted after long-term treatment. These changes reflect that CO2 dissolves in the macromolecular network and acts as a solvent allowing a rearrangement of the network. Nanoindentation directly confirmed the softening effects of CO2 on nanoscale mechanical properties, including Young's modulus, hardness, and fracture toughness. Interestingly, all these changes were reversible to some extent after removing CO2 from coal. These findings provide new evidence for clarifying the polymeric macromolecular structure of coal and directly demonstrated the softening effects of CO2 on the macromolecular structure. Highlights: Softening effects of CO2 on coal is first confirmed in nanoscale. Coal surface becomes cracked and highly distorted after interacting with CO2 . Changes in structural and mechanical properties are reversible to some extent after CO2 removal.